Analisis Faktor Sosial Ekonomi dan Demografi terhadap Kemiskinan di Kota Langsa - Asnidar; Safuridar; Puti Andiny (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
The aim of this research is to analyze the influence of socio-economic factors (education and per capita income) and demographics (dependency ratio and sex ratio) on poverty in Langsa City, both partially and simultaneously. This research uses secondary data obtained from the Langsa City Central Statistics Agency. The data analysis method in this research uses the classical assumption test, multiple linear regression, t test, F test and coefficient of determination test. The research results show that partially socio-economic factors, namely the education variable, have a negative and insignificant effect on poverty in Langsa City, and the per capita income variable has a negative and significant effect on poverty in Langsa City. Meanwhile, partially demographic factors, namely the sex ratio variable, have a negative and insignificant effect on poverty in Langsa City, and the dependency ratio variable partially has a negative and significant effect on poverty in Langsa City. Simultaneously, socio-economic and demographic factors have a significant effect on poverty in Langsa City. Limitations in this research include that the variables used do not include all variables that influence poverty, so it’s hoped that future researchers can add other relevant bariables that influence poverty over a longer research period.